The Infill House - Kyle Kinsman (Oz, 1995)
The paradoxical question posed by this issue's theme, namely, can any system of design values be relevant in a multicultural world, is cleverly constructed for the way in which it places the consideration of design squarely within the context of topical social issues. The scope of the discussion is expanded beyond that of a more narrow formalist discourse and instead implies the consideration of the built object's end-users, that is, those persons who experience buildings as part of the environment within which their lives unfold.